Low-power, high-speed sram design: A review - Tan, Soon-Hwei; Loh, Poh-Yee; Mohd-Shahiman, Sulaiman; Yusoff, Zubaida (SOC MICROELECTRONICS, 2007)
This article describes the challenges in the design of low-power SRAM and difficulties in designing a high-speed static RAM, Following an overview of general issues, approaches/techniques in achieving low-power SRAM, as well as techniques to increase SRAM operating frequency are described. Following the overview of each approach, the challenges and trade-offs are outlined.